Effects of liberal education on students' personality, critical thinking, and leadership skills: A conceptual study - Jing Yi Zhao; Soon Singh Bikar Singh (Malaysian Journal of Social Sciences and Humanities (MJSSH), 2024)
The concept of liberal education emerged in the 19th century when scholars in Europe and the United States recognized that the academic departments of modern universities were overly specialized, leading to a fragmented understanding of knowledge. China is home to several esteemed national universities that offer liberal arts programmes, including Peking University (established in 2007), Sun Yat-sen University in Guangzhou (established in 2009), and Fudan College at Fudan University in Shanghai (opened in 2012). As the popularity of liberal education continues to grow on a global scale, an increasing number of educational institutions are offering specialised liberal education courses. However, students do not perform as well as they could. The objectives of this research project are the critical thinking, personality and leadership factors and their influence on student performance in liberal education courses.